2017
DOI: 10.1093/femspd/ftx087
|View full text |Cite
|
Sign up to set email alerts
|

The clinical recovery of tuberculosis patients undergoing specific treatment is associated with changes in the immune and neuroendocrine responses

Abstract: Tuberculosis (TB) caused by Mycobacterium tuberculosis is a health problem worldwide. Patients with pulmonary TB show a neuro-immune-endocrine imbalance characterized by an impaired cellular immunity together with increased plasma levels of cortisol, pro- and anti-inflammatory cytokines and markedly decreased dehydroepiandrosterone (DHEA) levels. Extending these findings, we now investigated the immune-endocrine profile of TB patients undergoing specific treatment. Patients (n = 24) were bled at diagnosis (T0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
6
19
0
1
Order By: Relevance
“…As in previous studies (32)(33)(34), patients with only TB showed decreased blastogenesis, which in turn correlated negatively with IL-10 levels, a cytokine of recognized inhibitory effect on lymphoproliferation (35). Such decreased specific proliferation may be partly attributed to a recruitment of cells committed toward the site of the lesion (19).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As in previous studies (32)(33)(34), patients with only TB showed decreased blastogenesis, which in turn correlated negatively with IL-10 levels, a cytokine of recognized inhibitory effect on lymphoproliferation (35). Such decreased specific proliferation may be partly attributed to a recruitment of cells committed toward the site of the lesion (19).…”
Section: Discussionsupporting
confidence: 71%
“…As seen in former studies (33,34,47,48), the unbalanced relationship between steroid hormones recorded in TB patients, increased and decreased levels of cortisol and DHEA-DHEA-S, respectively, was also found in TB+DM patients. This may be explained by assuming that the adrenal gland is trying to preserve cortisol production at the expense of DHEA synthesis, to counteract the inflammatory response accompanying active disease.…”
Section: Discussionsupporting
confidence: 66%
“…Although promising, further research is needed to establish the efficacy of this new assay as marker for treatment monitoring and/or outcome. 166,195,196] [158] [172,173,197] [ 162,175] Markers of lung tissue repair (platelet activity VEGF, TGF-β, MMPs) [195,196] [135].…”
Section: T-cell Responsesmentioning
confidence: 99%
“…Additional candidates are the evaluation of the proportions of M. tuberculosis-specific CD27low CD4 + T-cells, which decline in parallel to the reduction of lung tissue damage [65]. Other potential serum markers are vascular endothelial growth factor, matrix metalloproteinase-9, transforming growth factor (TGF)-β1 and aminoterminal propeptide of type III procollagen (PIIINP) [172][173][174][175][176]. [177][178][179][180][181], but also in cohorts containing both HIV-co-infected and HIV-uninfected individuals [182].…”
Section: Modulation Of Monocytic and Lymphocytic Cell Populationsmentioning
confidence: 99%
“…Although at the experimental level low GCs concentrations may rescue thymocytes from the TCR-mediated apoptosis ( 81 , 82 ), the scenario in TB patients is characterized by a chronic elevation of cortisol that while being of moderate intensity remained so even after several months of treatment initiation ( 83 ). Furthermore, TB patients also present quite reduced amounts of circulating leptin levels ( 45 ).…”
Section: Thymus Involvement In Tb Facts and Hypothesismentioning
confidence: 99%